Improved performance of 1.3-μm multilayer P-doped InAs/InGaAs quantum dot lasers using rapid thermal annealing - Cao, Qi (2013)
Significant improvements in the performance of p-doped ten-layer InAs/InGaAs quantum dot laser are demonstrated using rapid thermal annealing at 600 °C. The annealed laser shows about 2.7 times increase in the saturated output power and external differential quantum efficiency without obvious wavelength shift. Decrease in internal loss of 2.9 cm-1 and improvement in the threshold current by 23% are achieved. Defect reduction is thought to be the most likely mechanism contributing to the improved performance according to the electroluminescence and improved characteristic temperature behavior.